Meiotic transmission of a hypomethylated repetitive DNA family in tobacco - Vyskot, B; Koukalová, B; Kovařík, A; Sachambula, L; Reynolds, D; Bezděk, M (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 1995)
We have recently shown that hypomethylation of cytosine residues in the HRS60 family of repetitive DNA sequences can be induced with 5-azacytidine (5-azaC) in tobacco tissue cultures. We have also proven that such a DNA methylation status is maintained during the recovery of protoplasts, plant regeneration, and vegetative development. In the present paper we follow meiotic transmission of hypomethylated HRS60 DNA. Plants obtained from seeds treated with 5-azaC were either self pollinated or crossed with a non-treated control in a reciprocal way. Analysis of the methylation status of the HRS60 DNA revealed that these sequences were hypomethylated in the progenies up to the extent found in the parental 5-azaC-treated plant. Since no parent-of-origin effect was observed, we presume that both male and female gametes transmit an artificial methylation imprint to a similar extent. This result is supported by methylcytosine evaluation in the total genomic DNA samples. A temporal analysis of 5-azaC effects on germinating seeds and a phenotypic evaluation of 5-azaC-treated tobacco plants are also presented.